Estudo do efeito citotóxico de chalc6a na linhagem celular de carcinoma de coloretal humano HCT-116 - Carvalho, Mylena Costa da Silva de (2021)
The antitumor treatment currently available represents a major scientific breakthrough in the fight against cancer. Despite this, there are still many adverse effects concomitant with the therapeutic effect and/or a high rate of resistance to chemotherapy treatment. In addition, statistics have shown that cancer remains a serious public health problem and, therefore, deserves special attention, reinforcing the need to develop more effective anticancer molecules with less adverse effects. In this context, the chemical class of chalcones has been the target of interest for many researchers, who have synthesized countless molecules with promising antitumor effects in vitro and in vivo. Based on a previous study of a series of 20 chalcones, a small molecule (Chalc6a) with strong cytotoxic activity in human colorectal carcinoma cell line HCT-116 (IC50 = 3.56 ± 0.73 μM) was identified. Thus, the general objective of the present work was to study the cytotoxic effect of Chalc6a on human tumor cells, especially the HCT-116 strain, aiming at the development of a new compound with anticancer potential. The results of the MTT test revealed strong cytotoxic activity for Chalc6a in different human tumor cell lines after 72 h of incubation with IC50 values ranging from 5.65 to 10.52 μM. During this incubation time, no cytotoxic effect was observed in a non-tumor model L-929 (IC50 > 20 μM). After 48 and 24 h of incubation with HCT-116 tumor cells, Chalc6a showed IC50 values of 5.67 and 9.81μM, respectively, which, together with the IC50 of 72 h, suggest a time-dependent cytotoxic effect. Trying to analyze the beginning of the cytotoxic effect promoted by the test compound, morphological and flow cytometric analyzes were performed after 24 h of incubation of HCT-116 cells treated with Chalc6a. The results revealed induction of apoptosis independent of mitochondrial depolarization related to cell cycle arrest in the G2 / M phase. Thus, the present study corroborates the anti-tumor cytotoxic potential of Chalc6a in HCT-116 cell line, enabling the advancement of its study using in vivo models.